2007
DOI: 10.1161/01.str.0000258112.14918.24
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Recanalization on Ischemic Stroke Outcome

Abstract: Background and Purpose-For a biomarker to serve as an auxiliary or surrogate outcome measure, it must be tightly correlated with and causally related to functional clinical outcome. Vessel recanalization is a potential surrogate outcome marker for functional outcome in trials of thrombolytic and mechanical recanalization therapies in acute stroke, but the correlation of recanalization and clinical outcome has not been previously systematically reviewed. Methods-Through Medline search, we identified and abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
987
4
46

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,353 publications
(1,068 citation statements)
references
References 22 publications
31
987
4
46
Order By: Relevance
“…2015a). Previous studies indicated a high predictive value of successful reperfusion (Rha and Saver 2007) and pretreatment CT‐angiographic collateral status (Miteff et al. 2009; Lima et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2015a). Previous studies indicated a high predictive value of successful reperfusion (Rha and Saver 2007) and pretreatment CT‐angiographic collateral status (Miteff et al. 2009; Lima et al.…”
Section: Discussionmentioning
confidence: 97%
“…2011). Besides collateral status, recanalization is strongly associated with improved functional outcomes and reduced mortality (Rha and Saver 2007), more specifically, substantial angiographic reperfusion seems to be the best predictor for independence after 3 months (Yoo et al. 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As intracranial vessels may become stenotic or occluded due to both atherosclerotic and embolic disease, we did not etiologically group them as LAA, but as a separate group. Spontaneous recanalization of emboli in the intracranial arteries will often occur, but may happen both in the acute phase and days and weeks after the initial stroke (Rha & Saver, 2007). As a result of this, it may be difficult to discriminate between LAA and CE as cause of an intracranial lesion in the first weeks and months after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with carotid occlusion–associated stroke have high rates of death and disability but treatments are limited. Successful recanalization with intravenous tissue plasminogen activator (tPA), the current stroke thrombolytic, is only achieved in 10% to 30% of patients with carotid occlusion 1, 2, 3. Although a severe carotid stenosis predicts a greater risk of stroke for any individual,4 the population frequency of mild stenosis is greater.…”
Section: Introductionmentioning
confidence: 99%